Reduction of liver mass due to malnutrition in rats: correlation with emaciation of animals and size of organs not inserted in the portal system - Parra, Osório Miguel; Hernandez-Blasquez, Francisco Javier; Silva, Rubens Augusto Penteado de Sousa e; Silva, José Roberto Machado Cunha da; Peduto, Luigi; Soares, Magna Maltauro; Saad, William Abrão; Saad Junior , William Abrão (São Paulo Medical Journal, 1995)
We studied the effects of protein-energy malnutrition on the liver morphology of rats as compared to animal emaciation and to reduction in size of the organs not irrigated by splanchnic blood such as kidneys and spleen. The animals were divided into two groups, one of them fed ad libitum rate (N=10) and the other (N=14) receiving water but no food for 7 days, and the changes in animal weight, liver, kidney and spleen mass were determined. DNA and the protein/DNA ratio, as well as hepatocyte size, were determined in liver tissue. The liver decreased in mass (27.14%) at a significantly higher proportion (p<0.05) when compared to body emaciation (19.22%). Similar to the reduction in body weight, the masses of kidneys and spleen were reduced by 18.68% and 24.28%, respectively. The reduction in liver mass occurred due to hypoplasia and atrophy, i.e., a decrease in hepatocyte number and size, respectively. We conclude that there is a preferential consumption of liver protein in protein-energy malnutrition which is suggested to result from the additive action of the effects of overall consumption of organic reserves due to malnutrition proper and to the reduction of the hepatotrophic stimulus.